The Ca2+-activated cation channel TRPM4 is a negative regulator of angiotensin II-induced cardiac hypertrophy - Kecskés, Miklós; Jacobs, Griet; Kerselaers, Sara; Syam, Ninda; Menigoz, Aurélie; Vangheluwe, Peter; Freichel, Marc; Flockerzi, Veit; Voets, Thomas; Vennekens, Rudi (Basic research in cardiology, 2015)
Cardiac muscle adapts to hemodynamic stress by altering myocyte size and function, resulting in cardiac hypertrophy. Alteration in myocyte calcium homeostasis is known to be an initial signal in cardiac hypertrophy signaling. Transient receptor potential melastatin 4 protein (TRPM4) is a calcium-activated non-selective cation channel, which plays a role in regulating calcium influx and calcium-dependent cell functions in many cell types including cardiomyocytes. Selective deletion of TRPM4 from the heart muscle in mice resulted in an increased hypertrophic growth after chronic angiotensin (AngII) treatment, compared to WT mice. The enhanced hypertrophic response was also traceable by the increased expression of hypertrophy-related genes like Rcan1, ANP, and α-Actin. Intracellular calcium measurements on isolated ventricular myocytes showed significantly increased store-operated calcium entry upon AngII treatment in myocytes lacking the TRPM4 channel. Elevated intracellular calcium is a key factor in the development of pathological cardiac hypertrophy, leading to the activation of intracellular signaling pathways. In agreement with this, we observed significantly higher Rcan1 mRNA level, calcineurin enzyme activity and protein level in lysates from TRPM4-deficient mice heart compared to WT after AngII treatment. Collectively, these observations are consistent with a model in which TRPM4 is a regulator of calcium homeostasis in cardiomyocytes after AngII stimulation. TRPM4 contributes to the regulation of driving force for store-operated calcium entry and thereby the activation of the calcineurin-NFAT pathway and the development of pathological hypertrophy.
Im Titel ist "2+" hochgestellt
Gesehen am 07.07.2020